Japanese Society and Lay Participation in Criminal Justice Social Attitudes, Trust, and Mass Media - Fujita, Masahiro (Springer Singapore, 2018)
This book describes the state of the lay participation system in criminal justice, saiban-in seido, in Japanese society. Starting with descriptions of the outlines of lay participation in the Japanese criminal justice system, the book deals with the questions of what the lay participants think about the system after their participation, how the general public evaluate the system, whether the introduction of lay participation has promoted trust in the justice system in Japan, and the foci of Japanese society's interest in the lay participation system. To answer these questions, the author utilizes data obtained from social surveys of actual participants and of the general public. The book also explores the results of quantitative text analyses of newspaper articles. With those data, the author describes how Japanese society evaluates the implementation of the system and discusses whether the system promotes democratic values in Japan. Masahiro Fujita is a Professor of Social Psychology in the Faculty of Sociology at Kansai University. .